Principles of innovation to build nutrition-sensitive food systems in South Asia. (January 2019) - Glover, Dominic; Poole, Nigel
Highlights: Innovation is a development policy buzzword. Policy makers seek innovations in agri-food systems to improve nutritional outcomes. The 'triple burden of malnutrition' is an outcome of previous innovations. Policy should heed the direction, distribution and diversity of innovations. South Asia has an opportunity to shape socio-technical change in agri-food systems. Abstract: Innovations within global food systems have contributed to the predicament known as the triple burden of malnutrition – the co-existence of hunger and micronutrient deficiency with the diseases of overnutrition, such as obesity, diabetes and hypertension. We use the case of the triple burden in South Asia to demonstrate analytically that innovation is a double-edged sword, with positive and negative potential, rather than a simple good. To achieve the Sustainable Development Goals that target food and nutrition security and sustainable agriculture (e.g. SDGs 2, 3 and 12), the countries of South Asia need more innovation, but, first, they would also benefit from some intelligent reflection about what innovation means, the directions it should take, and its risks and downsides alongside its benefits. In the present juncture, South Asian countries have an opportunity to learn from the experiences of other developing nations, and choose from alternative options to steer their own course. In this paper, we discuss how innovation has contributed to the present situation and ask how alternative kinds of innovation may enable South Asian countries to escape from the triple burden. We describe a conceptual framework that may be useful for thinking about how innovation pathways can be created and directed towards the goal of improving nutritional outcomes in South Asia. The framework draws attention to the direction of socio-technical change, the distribution of technologies and their risks and benefits, and the diversity of possible innovation pathways (STEPS Centre, 2010). We illustrate these points using examples of innovations in the areas of agricultural production, value chain interventions, and policy and institutional reforms.